A Survey of Imidacloprid Levels in Water Sources Potentially Frequented by Honeybees (Apis mellifera) in the Eastern USA - Johnson, J. D. (Water Air Soil Pollut, 2014)
Imidacloprid, a water-soluble neonicotinoid pesticide used globally in many applications, has been the subject of numerous studies (1) to determine its sublethal effects (5–100 ppb, LD(50) ∼200 ppb) on honeybees. This study was undertaken to determine, by ELISA assay, the presence of imidacloprid in water sources potentially frequented by honeybees in urban, suburban, and rural environments across the state of Maryland. Eighteen sites (six samples/site) were chosen which spanned diverse habitats including golf courses, nursery, livestock and crop farms, residential neighborhoods, and cityscapes. Hives were present either at or within 0.5 miles of each site. Imidacloprid was quantifiable in 8 % of the samples at sublethal levels (7–131 ppb). They were not clustered at any one type of site. Results for 13 % of the samples were at the threshold of detection; all others were below the detection limit of the assay (<0.2 ppb).